PECULIARITIES OF BUSINESS ASSET MANAGEMENT - О.Г. Головко; Д.О. Омеляненко (Економіка та право)
The article is devoted to the generalization of theoretical aspects and practical recommendations for improving the asset management system in modern conditions. To build an effective system, the object of management — assets — is studied in detail. The approaches to understanding the essence of assets, namely value, financial and property, are singled out. The ratio of such concepts as “current assets”, “working capital” and “working capital” is studied, their common and different characteristics are determined. The current assets are grouped according to different classification features and their significance in the production process is determined. It is substantiated that the grouping of current assets is primarily of practical importance, allowing to build a clear system of accounting and analysis of the availability and movement of current assets and to form an effective system of their management by individual types. A thorough analysis of the interpretations of the concept of “asset management” available in the scientific literature has been made, and several approaches to its understanding have been identified. The conducted research made it possible to form an author's definition of the current assets management system. It is determined that the current assets management system should be based on an integrated approach, the components of which are objects and subjects of management, purpose, basic principles and functions, methods and tools of influence, formalized quantitative and qualitative criteria for achieving goals, and factors forming the operating environment of the object. The characteristic of each element of the system is given, in particular the subjects and objects of management are concretized, their interaction is considered, the purposes and tasks are outlined. It is determined that the functions of the management system are controlling, stabilizing and analytical, and the principles on which it is based — timeliness, unity, continuity, optimality and rationality. The implementation of the current assets management system involves the implementation of a number of successive measures in the form of certain stages, which are considered in the work. The proposed system of current assets management will predict the choice of management strategy of the entity in the long run and increase the overall efficiency of its operation.